Parents' anticipated responses to children's cyberbullying experiences; Action, Education and Emotion. (May 2022) - Stuart, Jaimee; Scott, Riley; Smith, Calvin; Speechley, Molly
Highlights: Parents anticipate that they will take action by reporting, restricting, or investigating the incident if their child were to be cybervictimized. Parents anticipate that they will take action and communicate with or educate their child if they were to be perpetrator of cyberbullying. Regardless of the role in cyberbullying, most parents endorsed restrictive actions either to protect their child or to punish them. Patterns of parental responses may reduce disclosure of cyberbullying. Abstract: Despite the critical role of parents in the prevention of bullying, there is little evidence regarding how parents anticipate they will respond to their child's engagement in cyberbullying as either a victim or perpetrator. The current study aimed to address this gap by qualitatively exploring parents imagined reactions to cyberbullying among parents of adolescents aged 12–16 years old. The answers of parents who indicated that their child was not currently, or had not previously, been involved in bullying were included in the study. The overall corpus of data included 406 responses concerning victimization and 452 concerning perpetration. Data were thematically analyzed and found to present three core themes; Taking Action (anticipated behaviors to stop the occurrence or minimize the negative outcomes of bullying), Communication and Education (focus on understanding the context in which the bullying occurred and offering support), and Emotional Reactions (the parents' own emotional responses to imagined cyberbullying). Descriptive data indicated that Taking Action was the most frequently anticipated response to cyber victimization and Communication and Education was the most frequently anticipated response to cyberbullying. Additionally, there was evidence for patterns of responses to both victimization and perpetration with 34.4% of parents endorsing Taking Action under both conditions and 22.6% endorsing Taking Action for perpetration coupled with Communication and Education for victimization. The findings are discussed in relation to promoting disclosure and developing effective prevention of cyberbullying.